The Central American species of Euglossa subgenus Glossura Cockerell, 1917 (Hymenoptera, Apidae) - Moure, J. S. (1967)
This is one of three papers on the Central American Euglossine bees belonging to the genus Euglossa Latreille, and deals with the species of the subgenus Glossura.